Unmasking BRASH Syndrome: A Rare and Reversible Cause of Cardiovascular Collapse in the Elderly - Milhan El-Yamani Karim; Tawang Handayani; Hardianti Hardmi Putri; Setiawan Widodo (HM Publisher, 2025)
Background: BRASH syndrome (Bradycardia, Renal failure, AV nodal blockade, Shock, and Hyperkalemia) is an increasingly recognized but still underdiagnosed condition, particularly in elderly patients with multiple comorbidities and those taking AV nodal blocking agents. It represents a synergistic interplay between these factors, leading to a potentially life-threatening state of cardiovascular collapse. This case report aims to highlight the clinical presentation, diagnostic challenges, and successful management of BRASH syndrome in an elderly female patient. Case presentation: A 65-year-old female with a history of stage 4 chronic kidney disease and congestive heart failure (ejection fraction of 65%) presented to the emergency department with worsening vomiting over the past week, generalized weakness, dizziness, and palpitations. Her medication list included amlodipine, bisoprolol, candesartan, nitrokaf, furosemide, and aminoral. On examination, she was hypotensive with a blood pressure of 90/60 mmHg and bradycardic with a heart rate of 40 beats per minute. An electrocardiogram (ECG) revealed a junctional escape rhythm with a heart rate of 38 beats per minute and a left bundle branch block. Laboratory investigations showed severe hyperkalemia (potassium 8.1 mmol/L), hyponatremia (sodium 113 mmol/L), elevated creatinine (4.06 mg/dL), and urea (112.3 mg/dL). Conclusion: This case underscores the importance of recognizing BRASH syndrome as a distinct clinical entity, especially in elderly patients with pre-existing cardiac and renal conditions who are on AV nodal blocking medications. Prompt diagnosis and management, focusing on correcting hyperkalemia, discontinuing offending medications, and providing supportive care, can lead to favorable outcomes and prevent potentially fatal complications. Increased awareness and further research are crucial for establishing standardized guidelines for the diagnosis and management of this underrecognized syndrome.